Bases farmacocinéticas, bioquímicas y moleculares de la participación del transportador de eflujo ABCG2/BCRP en el pasaje transplacentario de zidovudina - Filia, María Fernanda (2017)
The aim of this work was to evaluate the participation of the ATP-binding cassette efflux transporter ABCG2/BCRP in transplacental AZT distribution and the relevance for drug safety, as compared with 3TC. Oral daily doses of AZT (60 mg/kg), 3TC (30 mg/kg) or vehicle (VEH) were administered between E11 and E20 to pregnant rats. ABCG2 expression in placenta and fetus (liver and brain) was selectively induced by AZT. Both drugs equally damaged nuclear DNA in maternal blood, bur 3TC was significantly more deleterious than AZT in fetal liver. Only 3TC treatment significantly altered mitochondrial function in fetal brain. At E21, AZT- or VEH-treated animals received 60 mg AZT/kg iv in the presence or not of the ABCG2 inhibitor gefitinib (20 mg/kg, ip). The AUC of AZT significantly decreased in fetal brains isolated from AZT-exposed fetuses compared to VEH-treated group, but this effect was abolished by ABCG2 inhibition. Our results suggest that the absence of mitochondrial toxicity in the fetal brain after chronic AZT, compared to 3TC, could be attributed to its low accumulation in the tissue caused by ABCG2 overexpression. We propose that any interference with ABCG2 activity would increase the amount of AZT reaching the fetal brain increasing the risk of brain toxicity.